Pengaruh Model Pembelajaran Search, Solve, Create, and Share (SSCS) terhadap Keterampilan Literasi Sains Peserta Didik - Anggraini, Wulan; Yurnetti, Yurnetti; Oktavia, Rani; Arif, Khairil (SEMESTA: Journal of Science Education and Teaching, 2025)
Contemporary science education aims to equip students with the competencies needed to address the complex challenges of the 21st century, particularly within the framework of Industry 4.0, where scientific literacy is recognized as a fundamental skill. However, students’ low levels of scientific literacy are often attributed to passive, text-based, and teacher-centered learning methods. This study aims to examine the effect of the Search, Solve, Create, and Share (SSCS) learning model on the scientific literacy of seventh-grade students at SMPN 5 Mandau in the topic Forms of Matter and Their Changes. The study employed a quasi-experimental design with a non-equivalent control group design. The sample consisted of two classes selected through purposive sampling. Research data were analyzed using descriptive and inferential statistics with the aid of Microsoft Excel. The results of the hypothesis testing revealed a significant difference in the average scores between the two classes after the implementation of the SSCS learning model. The posttest analysis showed that the calculated t-value (tcount = 2.458) was greater than the critical t-value (ttable = 2.004), indicating that the SSCS learning model had a significant positive effect on students’ scientific literacy.